Physiological, biochemical activities of cherelle wilt on three cocoa clones (Theobroma cacao) under two levels of soil fertilities - Endang Sri Dewi.HS HS; PRAPTO YUDONO; EKA TARWACA SUSILA PUTRA; BENITO HERU PURWANTO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Dewi HS ES, Ydono P, Putra ETS, Purwanto BH. 2020. Physiological, biochemical activities of cherelle wilt on three cocoa clones (Theobroma cacao) under two levels of soil fertilities. Biodiversitas 21: 187-194. Cherelle wilt is one of the diseases caused by physiological disorders. It results in loss of young pods by 70-90%. This study aims to reveal the correlation of physiological, biochemical activities of several cocoa clones with two soil fertility status. The study was conducted using a nested design with two blocks as replications. The soil fertility status was classified based on soil chemical status. This obtained two clusters of soil fertility, namely low soil fertility, high soil fertility. The second factor was cocoa clone, consisting of three clones, namely RCC 70, RCC 71, KKM 22. Variables measured were soil character, biochemistry of fresh, wilting cherelles, physiological activities, cherelle wilt, biochemical activities including sucrose content, reducing sugar, invertase activity. The data obtained were analyzed for their variance (ANOVA) with a 95% confidence level, tested using Tukey’s HSD there were significant differences between treatments. The results showed that high soil fertility status could increase contents of N, P, K, boron in leaves, increase nitrate reductase activity, chlorophyll contents, increase photosynthesis rate, suppress transpiration rate, increase assimilate transport from leaves to cherelle, increase enzyme invertase activity. RCC 70 clone indicated better physiological, biochemical activity, had the smallest percentage of cherelle wilt. Soil fertility status can suppress cherelle wilt by up to 60% through increasing physiological, biochemical activity. The RCC 70 clone shows the lowest cherelle wilt values ??compared to RCC 71, KKM 22 clones.